THE DEMAND FOR PUBLIC ACCOUNTANTS' SERVICES AND THE LEGAL IMPLICATIONS OF PROFESSIONAL ACCOUNTABILITY - Ulwan, Hassan Nasih; Hidayat, Solikhul (Jurnal Meta-Yuridis, 2025)
This study aims to further examine the legal accountability of public accountants in the Indonesian legal system. This study is important to conduct considering that the public accountant profession has a significant role in expressing opinions on fairness in all material matters, financial position, results of operations, changes in equity, and cash flows in accordance with generally accepted accounting principles in Indonesia. In other words, the responsibility of a public accountant is to provide a statement on the financial statements. Public accountants are responsible for planning and conducting audits to obtain reasonable assurance that the financial statements are free from material misstatements, whether caused by errors or fraud. Financial statements are the responsibility of management, and the public accountant profession cannot be punished simply. This study is a normative legal study. The data used are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection technique uses literature studies, while the data validation technique uses source criticism. The data were analyzed using the legal interpretation method to obtain answers to the questions studied. The results of the study indicate that a public accountant can have criminal and civil liability in carrying out his duties when publishing a company's financial statements.Keywords: criminal liability, civil liability, public accountant, financial statements.